The Ratanasuta : The Chanting To Exorcise Covid-19 - Sinsombat, Phra Santas; Sintabsan, Phuwadet; Tomgsuk, Chairat; Khwankhong , Chiraphot (Asia Pacific Journal of Religions and Cultures, 2021)
Rattanasuta is a chant to eliminate danger from starvation, pestilence, and undead. Buddhists treat as tradition to chant the sutra in order to eliminate diseases such as asthma. The verses of the sutra, including the sprinkle of holy water of parita with Buddha’s power, is extremely powerful It is able to help dispel 3 kinds of suffering, shortage of food, devil, and disease. As the world knows the new outbreak of Covid-19 virus, humans have to come back and review how to manage, prevent, and confront. This lesson is not the end. Many people die which bring a shock, panic, and fear within the human mind. In Thai society, there is also a talk about chanting the repulsion of Covid-19, which seems to be both positive and negative. Although evidence of rationality could not confirm that there is the Ratanasutra chanting in the Buddhist era. But with the power of the chanting made serious disasters in the past calm abruptly. It reminds one the similarities to the current events that Thai society is facing. Even today, the Thai Buddhist monk still chants the Ratana Sutra every time the Buddha’s water is made. That is the reason for the mention of important chanting in society. It is a proof that humans and religion continue to be related in all circumstances, from the past until the present.